A nonRD receptor‐like kinase prevents nodule early senescence and defense‐like reactions during symbiosis. Issue 4 (11th June 2014) - Berrabah, Fathi; Bourcy, Marie; Eschstruth, Alexis; Cayrel, Anne; Guefrachi, Ibtissem; Mergaert, Peter; Wen, Jiangqi; Jean, Viviane; Mysore, Kirankumar S.; Gourion, Benjamin; Ratet, Pascal
Summary Rhizobia and legumes establish symbiotic interactions leading to the production of root nodules, in which bacteria fix atmospheric nitrogen for the plant's benefit. This symbiosis is efficient because of the high rhizobia population within nodules. Here, we investigated how legumes accommodate such bacterial colonization. We used a reverse genetic approach to identify a Medicago truncatula gene, SymCRK, which encodes a cysteine‐rich receptor‐like kinase that is required for rhizobia maintenance within the plant cells, and performed detailed phenotypic analyses of the corresponding mutant. The Medicago truncatula symCRK mutant developed nonfunctional and necrotic nodules. A nonarginine asparate (nonRD) motif, typical of receptors involved in innate immunity, is present in the SymCRK kinase domain. Similar to the dnf2 mutant, bacteroid differentiation defect, defense‐like reactions and early senescence were observed in the symCRK nodules. However, the dnf2 and symCRK nodules differ by their degree of colonization, which is higher in symCRK. Furthermore, in contrast to dnf2, symCRK is not a conditional mutant. These results suggest that in M. truncatula at least two genes are involved in the symbiotic control of immunity. Furthermore, phenotype differences between the two mutants suggest that two distinct molecular mechanisms control suppression of plant immunity during nodulation.